Sport-related Concussion Incidence and Mechanism of Injury in Male and Female Players at the South African Youth Week Rugby Tournaments: 2011-2018 - Cardis, Sheenagh (Department of Health and Rehabilitation Sciences, 2022)
Background: Rugby is a popular international sport for male and female youth and adult players (6). Injury incidence including sport-related concussion (SRC) is high in youth rugby (7, 8) . This is concerning as youth are more vulnerable to SRC and take longer to recover from SRC than adults (9, 10). Females are also more susceptible to sustaining a SRC, take longer to recover from SRC and have a higher incidence of SRC complications than men (11-15). Most research has focused on SRC in adult male players. There are fewer studies on youth, in particular female youth. Further research into SRC in youth male and female players is thus required. Aim: The aim of this study was to determine the incidence and mechanism of SRC among youth male and female rugby players at the 2011 to 2018 and 2015 to 2018 South African Rugby Union Youth Week Tournaments respectively. Specific objectives: a) To determine the incidence of SRC among boys U13-U18 and girls U16-U18 players; b) To describe SRC mechanism of injury in boys U13-U18 and girls U16-U18 players; c) To determine if a difference in SRC incidence exists between boys U13-U18 and girls U16-U18 players, and also, between age groups; d) To determine if a difference in mechanism of SRC exists between boys U13-U18 and girls U16-U18 players, and also, whether the difference exists between age groups; and e) To describe l factors associated with SRC in boys U13-U18 and girls U16-U18 players. Methods: The study had a retrospective, epidemiological design. The study reviewed SRC injury data collected at the 2011-2018 South African Rugby Union Youth Week Rugby Tournaments. SRC injury data for boys was collected at the 2011-2018 South African Rugby Union Youth Week Rugby Tournaments. SRC injury data for girls was collected only at the 2015-2018 South African Rugby Union Youth Week Rugby Tournaments, as the girl's tournaments were only introduced in 2015. Results: Data from 266 SRC events were analysed in the study. Overall SRC incidence was 7.0 SRC per 1000 match playing hours (95% CI, 6.2.-7.8). Overall SRC incidence for boys was 6.9 SRC per 1000 match playing hours (95% CI, 6.0-7.8). Overall SRC incidence for girls was 7.9 SRC per 1000 match playing hours (95% CI, 5.3-9.9). There was no significant difference in SRC incidence between boys and girls. SRC incidence from 2011-2018 was 10.7 (95% CI, 8.2-13.1), 7.5 (95% CI, 5.5-9.6) and 5.3 (95% CI, 3.4-6.5) SRC per 1000 match playing hours for boys U13, U16 and U18 age groups respectively. SRC incidence from 2015- 2018 was 7.2 (95% CI, 3.7-10.2) and 7.9 (95% CI, 4.7-10.9) SRC per 1000 match playing hours for girls U16 and U18 age groups respectively. There was a significantly higher incidence of SRC in the boys U13 age group when comparing boys U13 and U18 age groups (IRR 2.0; 95% CI, 1.5-2.7; p=0.00014). Boys U13 players were twice as likely to sustain a SRC than their U18 counterparts. The tackle (65%) and ruck (20%) were responsible for the majority of SRC. Boys U13 players were significantly more likely to sustain a SRC from a tackle than boys U18 players (p= 0.01). Boys U16 players had a significantly greater incidence of SRC resulting from the ruck than boys U18 players (p=0.02). Overall the most common primary mechanisms of SRC were front-on tackles (27%) and collisions (18%). Boys U16 players had a significantly higher rate of SRCs due to front-on tackles than boys U18 players (p=0.00007). U16 boy players also had a significantly higher rate of SRCs caused by collisions than U18 boy players (p=0.00007). Similarly, boys U13 players had significantly higher incidences of SRCs due to collision than boys U18 players (p=0.003). Factors that were associated with SRC incidence were tournament day and the use of headgear. SRC was more likely to occur on day two than day four (p=0.0008), day five (p=0.0002) and day six (p<0.001). Players who did not wear headgear were more likely to sustain a concussion than those who did (p<0.001). Conclusion: Overall SRC incidence at the 2011 to 2018 South African Youth Week Rugby Tournaments was 7.0 SRC per 1000 match playing hours. This study is unique as it reports SRC incidence for youth female players. The overall SRC incidence for girls U16 and U18 groups was 7.7 SRC per 1000 match playing hours. As no significant difference was found for the incidence, injury event and mechanism of SRC between male and female players, similar injury prevention strategies can be implemented with these groups. Injury prevention strategies should focus on teaching safe contact technique in the tackle and ruck. Particular attention should be focused on teaching safe contact technique in U13 boys as the SRC incidence was highest in this group. Injury prevention strategies should also focus on teaching U13 and U16 boy players how to avoid collisions; and teaching U16 boy players how to execute safe front-on tackles and rucks. Further research should focus on identifying what aspects of the tackle and ruck result in SRC so more tailored and specific injury prevention strategies can be implemented.